Analisis Penentuan Harga Pokok Produksi Dengan Metode Full Costing Sebagai Dasar Penetapan Harga Jual Pada Cv Salwa Meubel - Bintang Komara Permana (Jurnal Akuntansi UMMI, 2020)
Calculation of the cost of production is an important thing to consider in determining the price of a product. Calculation of the cost of production is precise and accurate is the thing to do by any company, because without the calculation of the cost of production is right, a manufacturing company in question might have problems determining the selling price of a product. This study aims to determine the calculation of the cost of production and selling prices conducted by CV Salwa Furniture and analyze the calculation of the cost of production based on the order cost method Salwa CV Furniture, as well as determine the effect the cost of production of the determination of the selling price. The data used are primary data is a list of the production costs for the products produced during 2015. The sampling technique used is non probability sampling with purposive sampling approach. The variables tested were the cost of production with a full costing method as the independent variable (X) and the selling price as the dependent variable (Y). To test the hypothesis using contingency coefficient C which is to determine the level of significance between variables (X) to variable (Y). The conclusion of this study, Ho is rejected and Ha accepted, meaning that the cost of production is positive influence on the selling price.